Speech Act Analysis in “Mayonaka no Doa”: A Pragmatic Study of Japanese-English Bilingual Lyrics - Wiwik Retno Handayani (Universitas Sanata Dharma, 2025)
Analysis of speech acts in song lyrics is crucial to understanding how language functions as a communication tool rich in meaning and emotion. The Japanese song Mayonaka no Doa (Stay with Me), sung by Miki Matsubara in 1979, has now stolen attention again in the era of social media. Its repeated popularity on various platforms makes this song an interesting topic for study based on speech act theory. This research aims to recognize and examine the statements found in the song’s lyrics while also investigating how language use conveys the emotions and scenarios faced by the singer and how it connects with the feelings and experiences of the listeners. By doing so, this study seeks to highlight the profound impact of the song’s lyrics on both the performer and the audience, showing the ways in which language serves as a powerful emotional tool for communication. This research employs a distinctive qualitative descriptive analysis with a pragmatic perspective, distinguishing it from conventional studies in the discipline. The researcher assessed each verse of the lyrics to identify locution, illocution, and perlocution. The study results show that various locutionary speech acts play a role in conveying information, emotions, and circumstances. The illocutionary speech acts in these lyrics include expressive, directive, assertive, and commitment, each reflecting a complex communication dimension. In addition, the perlocutionary speech act indicates that the lyrics of this song have a profound emotional impact on the listeners, influencing their emotions, hopes, and thoughts. This finding illustrates the beauty of language in music and the audience’s active role in the communication process. It provides insight into how lyrics can serve as a means of deep emotional expression for listeners, strengthening the connection between music and human experience.